Current trends in modeling host–pathogen interactions. (25th February 2013) - Mukherjee, Sumanta; Sambarey, Awanti; Prashanthi, Karyala; Chandra, Nagasuma
Abstract: The rapid emergence of infectious diseases calls for immediate attention to determine practical solutions for intervention strategies. To this end, it becomes necessary to obtain a holistic view of the complex host–pathogen interactome. Advances in omics and related technology have resulted in massive generation of data for the interacting systems at unprecedented levels of detail. Systems‐level studies with the aid of mathematical tools contribute to a deeper understanding of biological systems, where intuitive reasoning alone does not suffice. In this review, we discuss different aspects of host–pathogen interactions (HPIs) and the available data resources and tools used to study them. We discuss in detail models of HPIs at various levels of abstraction, along with their applications and limitations. We also enlist a few case studies, which incorporate different modeling approaches, providing significant insights into disease. © 2013 Wiley Periodicals, Inc. This article is categorized under: Algorithmic Development > Biological Data Mining